Ilmu pendidikan dalam perspektif Islam - Tafsir, Ahmad (Bandung : Remaja Rosdakarya, 1992)
Educational system according to Islamic viewpoint, with reference to Indonesia.
Daftar pustaka : p. 206-208
Keywords: Islamic education -- Indonesia